Genetic ancestry as an effect modifier of naltrexone in smoking cessation among African Americans. Issue 6 (June 2015) - Bress, Adam; Kittles, Rick; Wing, Coady; Hooker, Stanley E.; King, Andrea
<x xml:space="preserve">Abstract</x> Objectives To determine whether there were differential quit rates between African Americans (AA) and European Americans with the experimental treatment naltrexone, and examine the role of genetic ancestry on these outcomes among AAs. Methods Data from a previous randomized trial of 315 smokers to naltrexone versus placebo were reanalyzed using West African (WA) genetic ancestry to define subpopulations. Logistic regression models were used to estimate treatment effects on early and end of treatment quit rates, by race and WA ancestry. Results Among European Americans (n=136), naltrexone significantly increased quit rates at 4 weeks (62 vs. 43%, P=0.03) with directional, but not statistically significant effects at 12 weeks (30 vs. 18%, P=0.12). In contrast, among the AAs (n=95), quit rates did not differ between naltrexone and placebo groups at either interval (4 weeks: 43 vs. 32%, P=0.27; 12 weeks: 22 vs. 18%, P=0.60). A median split was conducted in AAs for WA ancestry. Among AAs with low WA ancestry, quit rates were significantly higher with naltrexone compared with placebo (60 vs. 27%, P=0.03). There was no advantage in quit rates with naltrexone for the high WA ancestry group. Conclusion Naltrexone efficacy for smoking cessation varies across AA individuals with different levels of WA ancestry. These results suggest that genetic background may partially explain racial differences in drug response.